2017
DOI: 10.1007/s40708-017-0070-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimized statistical parametric mapping procedure for NIRS data contaminated by motion artifacts

Abstract: This study investigated the spatial distribution of brain activity on body schema (BS) modification induced by natural body motion using two versions of a hand-tracing task. In Task 1, participants traced Japanese Hiragana characters using the right forefinger, requiring no BS expansion. In Task 2, participants performed the tracing task with a long stick, requiring BS expansion. Spatial distribution was analyzed using general linear model (GLM)-based statistical parametric mapping of near-infrared spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…FNIRS uses near-infrared light to measure local concentration changes of deoxygenated hemoglobin (HbR) and oxygenated hemoglobin (HbO) from cortical brain areas which are seen as correlates of functional brain activity (Villringer et al, 1993; Sassaroli and Fantini, 2004). In comparison to HbO, HbR signals are considered to be less influenced by systemic physiological artifacts like cardiac pulsation, respiration, or Mayer wave fluctuations than HbO (Obrig et al, 2000; Zhang et al, 2005, 2009; Huppert et al, 2009; Suzuki, 2017). Other studies additionally reported that HbR tends to correlate stronger with blood oxygenation level dependent (BOLD) response than HbO (MacIntosh et al, 2003; Huppert et al, 2006; Schroeter et al, 2006; Foy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…FNIRS uses near-infrared light to measure local concentration changes of deoxygenated hemoglobin (HbR) and oxygenated hemoglobin (HbO) from cortical brain areas which are seen as correlates of functional brain activity (Villringer et al, 1993; Sassaroli and Fantini, 2004). In comparison to HbO, HbR signals are considered to be less influenced by systemic physiological artifacts like cardiac pulsation, respiration, or Mayer wave fluctuations than HbO (Obrig et al, 2000; Zhang et al, 2005, 2009; Huppert et al, 2009; Suzuki, 2017). Other studies additionally reported that HbR tends to correlate stronger with blood oxygenation level dependent (BOLD) response than HbO (MacIntosh et al, 2003; Huppert et al, 2006; Schroeter et al, 2006; Foy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The following fNIRS analysis was based on HbR signal, as HbR signals are considered to be less influenced by systemic physiological artifacts like cardiac pulsation, respiration, or Mayer wave fluctuations than HbO (Obrig et al, 2000 ; Zhang et al, 2005 , 2009 ; Huppert et al, 2009 ; Suzuki, 2017 ). Moreover, other studies reported that HbR tends to correlate stronger with the blood oxygenated level dependent (BOLD) response than HbO (MacIntosh et al, 2003 ; Huppert et al, 2006 ; Schroeter et al, 2006 ; Foy et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…In this article, the fNIRS analyses were based only on HbR signals, as these are considered to be less susceptible to systemic physiological artifacts like cardiac pulsation, respiration, or Mayer wave fluctuations than HbO (Obrig et al, 2000 ; Zhang et al, 2005 , 2009 ; Huppert et al, 2009 ; Suzuki, 2017 ). Moreover, other studies reported that HbR tends to correlate stronger with the blood oxygenated level dependent (BOLD) response than HbO (MacIntosh et al, 2003 ; Huppert et al, 2006 ; Schroeter et al, 2006 ; Foy et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%